FUNGSI KOORDINASI DALAM PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN GEMEH KABUPATEN KEPULAUAN TALAUD - SAIYA, ANSARI; Ogotan, Martha; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTCoordination is an important function of government management. The purpose of this study was todetermine how the implementation of the coordination function in governance in the sub Gemeh TalaudIslands. The method used is descriptive qualitative method. The informants who were interviewed as many as12 people are: sub-district, sub-district secretary, Head of Unit Department / Agency (4), Head of VerticalInstitutions (2), the village head (2), Leaders / Community Leaders (2). Data collection techniques used wereinterviews. Data was analyzed using qualitative descriptive analysis techniques-interactive model of Milesand Hubernann.Based on the results of the study conclude: 1. Coordination in the planning of programs / activitiesof governance among government agencies (Government of the District, SKPD and Agencies Vertical) in theDistrict Gemeh is good enough, which is done through the forum district level coordination meeting led andcoordinated by the Head, so as to realize the synchronization, harmony, harmony, balance, and overallintegrity of the programs / activities of government. (2) Coordination in the implementation of programs /activities in the district administration Gemeh is good enough, namely through: district level coordinationmeetings; demand for and delivery of data / information or report on progress in the implementation ofprograms / activities of all SKPD and agencies existing vertical; and through monitoring / monitoring Headof the implementation of the program / activity.Based on the conclusions suggested: (1) There must be communication reciprocal harmony betweenthe district governments (Head and his staff) with all the regional work units or SKPD (UPT Department /Agency and other work units), and Vertical Institutions in the region employment districts. (2) Head as theleader and coordinator of the sub-district government administration should seek to optimize the use ofmeans of coordination such as coordination meetings, demand and delivery of data / information between allgovernment work units in districts, and consulting.Keywords: Coordination, Government of the District.